Differential prognostic relevance of patho-anatomical factors among different tumor-biological subsets of breast cancer: Results from the adjuvant SUCCESS A study. (April 2019) - Deniz, Miriam; DeGregorio, Amelie; DeGregorio, Nikolaus; Bekes, Inga; Widschwendter, Peter; Schochter, Fabienne; Ernst, Kristina; Scholz, Christoph; Bauer, Emanuel CA.; Aivazova-Fuchs, Viktoria; Weissenbacher, Tobias; Kost, Bernd; et al.
Abstract: Objectives: In breast cancer, large tumor size, positive nodal stage and a triple-negative tumor subtype are associated with reduced survival, but the interactions between these prognostic factors are not well understood. Material and methods: Here we re-evaluated the impact of tumor size, nodal stage and tumor subtype on disease-free survival (DFS), overall survival (OS), distant disease-free survival (DDFS) and breast cancer specific survival (BCSS) in a retrospective analysis using data from the adjuvant SUCCESS A trial. Subgroup analyses were conducted to assess whether the effect of tumor size and nodal stage on survival depended on tumor subtype. Results: Increasing tumor size, higher nodal stage and triple negative breast cancer (TNBC) were associated with unfavorable prognosis (all p < 0.001). There was no significant interaction between tumor subtype and tumor size (p > 0.5 for all four survival endpoints), but we found significant interactions between tumor subtype and nodal stage (p < 0.05 for all four survival endpoints), with no differences in survival among tumor subtypes for patients with pN0 tumors (all p > 0.05) and pronounced differences in survival among tumor subtypes for patients with positive nodal stage (all p < 0.001). Conclusions: This analysis confirms tumor size, nodal stage and tumor subtype as independent prognostic factors in high-risk early breast cancer. Nodal-positive patients with TNBC had a considerably worse outcome compared to nodal-positive patients with another tumor subtype. This underlines the importance for early detection particularly for patients with TNBC. Trial registration: EudraCT 2005-000490-21;ClinicalTrials.gov Identifier: NCT02181101. Highlights: Tumor size, nodal stage and tumor subtype are independent prognostic factors in BC. Effect of biological subtype on survival not dependent on tumor size. Effect of biological subtype on survival dependent on nodal stage. Worst prognosis in advanced stage triple negative breast cancer.